Reproductive Biology of Puntius hexazona from the streams in the Riau University area and the upstream of the Sibam River - Padmayni, Padmayni; Windarti, Windarti; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPuntius hexazona (Sumatra fish) is a type of freshwater fish that inhabits the streams in the Riau University area and the upstream of the Sibam River. A study aims to understand the reproductive biology of P.hexazona has been conducted from May-August 2019. The fish was sampled 6 times, twice/month. Parameters measured were sexual characteristics, sex ratio, gonad maturity level, gonad somatic index (GSI), fecundity and egg diameter. Results shown that the fish from the streamswas 54 (24 males and 30 females,  sex ratio of 1: 1.25), while that of the Sibam River was 38 (16 males and 22 females, sex ratio of 1: 1.38). The average of GSI and fecundity of the fish from the streams was 3.37 and 432 respectively, while those of the Sibam River was 3.08 and 327. Egg diameter of all fish sampled was ranged from  0.33 to 0.78 mm. The eggs distribute evenly in the ovary an it indicates that the fish is a total spawner.Keywords: Sumatra fish, gonad maturity level, gonad somatic index, fecundity, total spawner.